2023
DOI: 10.1556/1326.2022.00999
|View full text |Cite
|
Sign up to set email alerts
|

A new simple liquid chromatographic assay for gentamicin in presence of methylparaben and propylparaben

Abstract: Gentamicin sulfate is a potent broad spectrum aminoglycoside antibiotic which is used against Gram-positive and Gram-negative bacteria. A simple, isocratic HPLC method for separation, identification and determination of gentamicin and parabens (methylparaben and propylparaben) was developed and validated. To our knowledge there is no report about simultaneous determination of those three analytes in pharmaceutical products. The optimum chromatographic conditions were achieved on CN column with a mobile phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Firstly, gentamicin is a complex mixture of five structurally distinct components (see Section 2). Secondly, gentamicin lacks chromophore groups, which means that it cannot absorb UV light and can be indirectly determined through chemical derivatization methods with o-phthaldialdehyde, phenyl isocyanate, 9-fluorenylmethyl chloroformate, 1-fluoro-2,4-dinitrobenzene, and others, which are timeconsuming and produce unstable derivatives [114,115]. Most of the literature on gentamicin release from PLGA and chitosan mentions derivatization with o-phthaldialdehyde or ninhydrin [11,30,63,[65][66][67].…”
Section: The Release Of Gentamicin From Polymeric Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, gentamicin is a complex mixture of five structurally distinct components (see Section 2). Secondly, gentamicin lacks chromophore groups, which means that it cannot absorb UV light and can be indirectly determined through chemical derivatization methods with o-phthaldialdehyde, phenyl isocyanate, 9-fluorenylmethyl chloroformate, 1-fluoro-2,4-dinitrobenzene, and others, which are timeconsuming and produce unstable derivatives [114,115]. Most of the literature on gentamicin release from PLGA and chitosan mentions derivatization with o-phthaldialdehyde or ninhydrin [11,30,63,[65][66][67].…”
Section: The Release Of Gentamicin From Polymeric Nanoparticlesmentioning
confidence: 99%
“…One of the most popular is the more rapid and cost-effective UV/VIS method. Alternatively, the most reliable method is high-performance liquid chromatography (HPLC), which enables UV, fluorescence, electrochemical, or MS detection [114,115].…”
Section: The Release Of Gentamicin From Polymeric Nanoparticlesmentioning
confidence: 99%
“…Gentamycin is one of the widest spectrum antibiotics used for the treatment of infectious diseases, is highly soluble in water and less soluble in organic solvents (Arhoutane et al 2019), and has an electrochemical activity due to the hydroxyl and amino groups. Ivkovic et al (2023) reported that evaporation, light scattering, and pulsed electrochemical detection methods were employed to detect gentamycin in water.…”
Section: Introductionmentioning
confidence: 99%
“…Gentamycin (GEN) is an aminoglycoside bactericidal, Figure 1 , works by inhibiting the synthesis of protein in bacteria [ 3 ], it was quantified via spectrophotometry [ 19 , 20 , 21 , 22 , 23 , 24 ],spectrofluorimetric [ 25 , 26 ], HPLC [ 27 , 28 , 29 ], and TLC [ 30 ].…”
Section: Introductionmentioning
confidence: 99%